Analysis of Factors Affecting Obedience of Pregnant Women in Conducting ANC Visits During the Covid-19 Pandemic - Habibah Matondang; Razia Begum Suroyo; Rina Hanum (Newinera Publisher, 2022)
The Covid-19 pandemic has made many changes, especially in the health sector. During this Covid-19 pandemic, pregnant women are required to have their pregnancy checked by a midwife or doctor, at least 6 visits. The Covid-19 pandemic has led to a decrease in visits by pregnant women to facilities due to several factors. The purpose of the study was to analyze the factors that influence the compliance of pregnant women in conducting ANC visits during the Covid-19 pandemic. This type of research is a mixed method (mixed method). This research was conducted in the working area of ​​Batu-Batu Health Center Subulussalam City with a population of 36 people and all of them were used as samples. The research informants were 13 people. Quantitative data analysis was performed using univariate, bivariate using chi-square and multivariate using multiple logistic regression at 95% confidence level (=0.05). Qualitative data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. The results showed that the factors that influenced the compliance of pregnant women in carrying out ANC visits during the Covid-19 pandemic in the Batu-Batu Health Center work area were attitude (p = 0.024), anxiety about infection (p = 0.020), information (p = 0.042), and communication/transportation infrastructure (p=0.045). Variables that have no effect are knowledge (p=0.197), and husband/family support (p=0.564). The most dominant factor influencing the compliance of pregnant women in conducting ANC visits during the Covid-19 pandemic in this study was the variable of anxiety about contracting Covid-19. Qualitatively, some pregnant women are worried about contracting Covid-19 because pregnant women are also vulnerable to contracting Covid-19 which poses a risk to pregnant women and the fetus they contain. What is unique is that pregnant women do not feel anxious because they do not have information about Covid-19 so that they continue to carry out pregnancy checks according to schedule. The leaders of the Batu-Batu Health Center are advised to socialize ANC visits at least 6 times with door to door counseling or create a WA or Facebook group so that correct information about ANC and Covid-19 is easier to reach and mothers do not experience excessive anxiety